2022
DOI: 10.1097/ju.0000000000002291
|View full text |Cite
|
Sign up to set email alerts
|

Supine versus Prone Percutaneous Nephrolithotomy for Complex Stones: A Multicenter Randomized Controlled Trial

Abstract: High-quality evidence comparing supine to prone percutaneous nephrolithotomy (PCNL) for the treatment of complex stones is lacking. This study aimed to compare the outcomes of supine (SUP) and prone (PRO) PCNL. Materials and Methods:A non-inferior randomized controlled trial was performed according to the CONSORT criteria. The inclusion criteria were patients over 18 years of age with complex stones. SUP was performed in the Barts flank-free modified position. Except for positioning, all the surgical parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Perrella et al (page 647) in a multi-institutional study report the first randomized, noninferiority trial comparing positioning with a primary outcome of success rate on the first postoperative day. 4 Their results illustrate similar early success rates but also describe some interesting secondary findings such as operative times and complications. The authors conclude that positioning during PCNL for complex kidney stones did not dramatically impact success, suggesting that advancing the less frequently utilized supine position may be worthwhile given some potential advantages.…”
Section: Supine Versus Prone Percutaneous Nephrolithotomy For Complex...mentioning
confidence: 54%
“…Perrella et al (page 647) in a multi-institutional study report the first randomized, noninferiority trial comparing positioning with a primary outcome of success rate on the first postoperative day. 4 Their results illustrate similar early success rates but also describe some interesting secondary findings such as operative times and complications. The authors conclude that positioning during PCNL for complex kidney stones did not dramatically impact success, suggesting that advancing the less frequently utilized supine position may be worthwhile given some potential advantages.…”
Section: Supine Versus Prone Percutaneous Nephrolithotomy For Complex...mentioning
confidence: 54%
“…Similarly, Perella et al found comparable outcomes for both prone and supine positioning in PCNL. Supine position was also associated with lower high-grade complication rates [ 27 ]. The downwardly orientated access sheath could have provided better drainage and prevented high intrarenal pressures, thus lowering infections in supine position [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with that, another advantage provided by supine position is the reduced operative time that might render mPCNL also more cost-effective. 5…”
Section: Editorial Commentmentioning
confidence: 99%